Reliance on double pedicle TRAM flap technique in breast reconstruction based on mammographic evidence - Fuat Yüksel; Emir Silit; Bahattin Çeliköz (Indian Journal of Plastic Surgery)
Breast reconstruction is now a part of the overall treatment of breast cancer. Its main drawback is rather the suspicion to conceal any probable recurrence. Fat necrosis is a particularly important finding because it can be mistaken for a local recurrence. Alternatively, local recurrences may be dismissed as areas of fat necrosis. Fat necrosis is a relatively minor complication of TRAM flap breast reconstruction but one that can induce anxiety, expense, and inconvenience for patients and concerns about tumor recurrence. The techniques selected for reconstruction must carry the least risks for these awful complications. 15 breast cancer cases were treated in our center by using Bostwick′s principles. These include double-pedicle technique in cases with one or two risk factors and added vascular delay two weeks prior to this procedure in cases with more risk factors. During the follow up period, neither the patients nor her physicians experienced any nodules in their treatment sites clinically. One case is the only exception that she felt hardness but it softened. Mammographically, no images of fat necrosis were observed in any of the cases. In contrary to other studies reporting no advantages of double pedicle technique to lessen the risk for fat necrosis, we observed fat necrosis only in one of 15 cases. This may be because both sides of the flap are supplied axially and delay procedures are added in high risk patients.